Bidirectional Tachycardia after an Acute Intravenous Administration of Digitalis for a Suicidal Gesture. (24th August 2014) - Sabatini, Diletta; Truscelli, Giovanni; Ciccaglioni, Antonio; Gaudio, Carlo; Grassi, Maria Caterina
Abstract : Acute digoxin intoxication is a life-threating condition associated with severe cardiotoxicity. Female gender, age, low lean body mass, hypertension, and renal insufficiency may worsen the prognosis. Arrhythmias caused by digitalis glycosides are characterized by an increased automaticity coupled with concomitant conduction delay. Bidirectional tachycardia is pathognomonic of digoxin intoxication, but it is rarely observed. An 83-year-old woman was admitted to the Emergency Department after self-administration of 5 mg of digoxin i.v. for suicidal purpose. Her digoxin serum concentration was 17.4 ng/mL. The patient developed a bidirectional tachycardia and the Poison Control Center of the hospital provided digoxin immune fab. Bidirectional tachycardia quickly reversed and the patient remained stable throughout the hospital stay. This case shows that a multiple disciplinary approach, involving cardiologists and toxicologists, is essential for the management of digoxin intoxication. The optimal treatment of this rare event depends on the clinical conditions and on the serum drug concentration of the patient. Digoxin immune fab represents a safe, effective, and specific method for rapidly reversing digitalis cardiotoxicity and should be started as soon as the diagnosis is defined.